On the Central Role of Small Farms in African Rural Development Strategies - Larson, Donald F. (World Bank E-Library Archive, 2016)
Improving the productivity of smallholder farms in Sub-Saharan Africa offers the best chance to reduce poverty among this generation of rural poor, by building on the limited resources farming households already possess. It is also the best and shortest path to meet rising food needs. Using examples from farmers' maize and rice fields, and comparisons with Asia, this paper examines why the set of technologies promoted to date have produced localized successes rather than transformational change. The paper explains the limitations of alternative policies that are not centered on small farms. It provides indicative examples of how resource-management technologies can supplement seed-fertilizer technologies to speed an African Green Revolution